MOLECULAR FIELD ANALYSIS AND DYNAMIC SIMULATION STUDIES OF 1,5-DISUBSTITUTED PYRAZOLINE-BASED MAO-A INHIBITORS FOR THE MANAGEMENT OF DEPRESSION - Abhimannu Shome; Pooja A. Chawla Naresh K. Rangra
Depression, along with grief and anxiety, is currently one of the most common mental illnesses. It was placed 25th among the major diseases. QSAR (CoMFA) of 37 compounds with MAO-A inhibitory activity yielded the most significant QSAR model, m.3, with r2 = 0.963, SDEC= 0.129, q2 = 0.742, SDEP= 0.34. Using the lead likeness matrix, thirty-seven 1,5-disubstituted MAO-A inhibitors were developed and tested based on the QSAR models. The top 13 compounds were identified. Furthermore, compound 2B (G: -10.3 kcal mol-1, RMSD: 0.151 Å) was selected among the top 13 hits obtained from molecular docking experiments. Significant interactions were also observed, including - contacts with Phe208, Tyr444, Trp407, and hydrogen bond interactions with Ala68 and Tyr69. Furthermore, dynamic modelling demonstrated that compound 2B (0.11 nm) has higher overall stability than clorgyline, with a lower RMSD value, and may reach equilibrium in the final 20-25 ns. In terms of RMSF, 2B produced around 0.34 nm with less variation than clorgyline. Throughout the simulation, 2B (No. of H-bond: 6) had more hydrogen bonding than clorgyline (No. of H-bond: 3) with the highest occupancy, i.e. 117.39% for GLU216, 29% for TYR444, and 49% for PRO72, and so on. Compound 2B was proven to be the most essential throughout the experiments. These new chemicals will be optimized in vitro and in vivo in the future. This study will surely contribute to the development of novel MAO-A inhibitors for the treatment of depression.